The Effect of Zikr Meditation on Anxiety, Stress Levels and Blood Pressure in Hypertensive Patients - Kurniawati, Erna Yovi; Sari, Dian Nirmala (Journal of Rural Community Nursing Practice, 2024)
Background: Hypertension, a prevalent chronic condition, poses significant health risks when left untreated. Psychological factors like stress and anxiety are known contributors to high blood pressure. Effective management of hypertension may benefit from non-pharmacological interventions that address these psychological elements. Purpose: This study aims to evaluate the impact of Zikr meditation, a spiritual mindfulness practice, on reducing anxiety, stress, and blood pressure in individuals with hypertension. Methods: A double-blind randomized controlled trial was conducted with 60 hypertensive patients, randomized into intervention and control groups. The intervention group participated in 20-minute Zikr meditation sessions for four weeks daily, while the control group engaged in a placebo activity. Anxiety and stress levels were measured using the Hamilton Anxiety Rating Scale (HAM-A) and the Perceived Stress Scale (PSS), respectively. Blood pressure readings were taken before and after the intervention. Results: Participants in the Zikr meditation group showed a significant reduction in anxiety and stress levels compared to the control group. Additionally, there was a notable decrease in systolic and diastolic blood pressure among those practicing Zikr meditation. Conclusions: Zikr meditation effectively reduces anxiety and stress, leading to lower blood pressure in hypertensive patients. These findings suggest that incorporating Zikr meditation into standard hypertension management could offer a valuable, non-pharmacological approach to improving cardiovascular health. Further research is recommended to examine Zikr meditation's long-term effects and broader applicability in hypertension care.